2022
DOI: 10.3390/pharmaceutics14030654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacokinetic and Pharmacodynamic Properties of Monoclonal Antibodies in the Management of Psoriasis

Abstract: The treatment of psoriasis has been revolutionized by the emergence of biological therapies. Monoclonal antibodies (mAb) generally have complex pharmacokinetic (PK) properties with nonlinear distribution and elimination. In recent years, several population pharmacokinetic/pharmacodynamic (PK/PD) models capable of describing different types of mAb have been published. This study aims to summarize the findings of a literature search about population PK/PD modeling and therapeutic drug monitoring (TDM) of mAb in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 155 publications
0
15
0
Order By: Relevance
“…The higher RSE% was also observed in Brodalumab (49.7%) and Ixekizumab (60.3%) ( Salinger et al, 2014 ; Tham et al, 2014 ), this is because the subpopulations of the responder and non-responder make the distribution of the post hoc IC 50 parameter as a bimodal distribution ( Zhou et al, 2010 ; Tham et al, 2014 ; Pan et al, 2020 ), but in our study, the sample size was too small to distinguish two subpopulations. K in and K out were parameters that related to the disease, the reported K in was 0.615–0.890 PASI/day, K out was 0.0313–0.064 day −1 ( Zhou et al, 2010 ; Salinger et al, 2014 ; Tham et al, 2014 ; Rodriguez-Fernandez et al, 2022 ). In our study, K in was 0.474 PASI/day, K out was 0.024 day −1 , and both of them were lower than those reported in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The higher RSE% was also observed in Brodalumab (49.7%) and Ixekizumab (60.3%) ( Salinger et al, 2014 ; Tham et al, 2014 ), this is because the subpopulations of the responder and non-responder make the distribution of the post hoc IC 50 parameter as a bimodal distribution ( Zhou et al, 2010 ; Tham et al, 2014 ; Pan et al, 2020 ), but in our study, the sample size was too small to distinguish two subpopulations. K in and K out were parameters that related to the disease, the reported K in was 0.615–0.890 PASI/day, K out was 0.0313–0.064 day −1 ( Zhou et al, 2010 ; Salinger et al, 2014 ; Tham et al, 2014 ; Rodriguez-Fernandez et al, 2022 ). In our study, K in was 0.474 PASI/day, K out was 0.024 day −1 , and both of them were lower than those reported in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Although the pathogenesis of psoriasis is still not fully elucidated, molecular and genetic studies have identified the main inflammatory pathways involved in the pathogenesis of psoriasis ( Rendon and Schakel 2019 ). Several mAbs designed to block either specific receptors or soluble mediators of the main pathways were approved for treating psoriasis, including TNF-α, IL-12/23, and IL-17 antibodies ( Rodriguez-Fernandez et al, 2022 ). Secukinumab, ixekizumab, and brodalumab are three anti-IL-17 mAbs which are already available in the market ( Mrowietz et al, 2021 ), AK111 is also targeting IL-17A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One step further towards dose optimization of biologics would be therapeutic drug monitoring (TDM), in which therapeutic decision making is guided by drug concentration measurements. 8 Aiming to develop a TDM strategy for secukinumab in psoriasis, Soenen et al confirmed the secukinumab underexposure in real-world overweight patients and determined a minimal effective secukinumab threshold of 39Á1 mg L -1 associated with achieving PASI ≤ 2 or DPASI ≥ 90%. 9 This trial provides high-quality evidence to support above-label dosing of secukinumab to improve treatment outcomes in an otherwise difficult-to-treat patient population.…”
mentioning
confidence: 99%